Targeting the imperfections at the ZnO/CsPbI2Br interface for low-temperature carbon-based perovskite solar cells. Issue 17 (17th April 2023) - Zhang, Xiang; Zhang, Dan; Guo, Tonghui; Zou, Junjie; Jin, Junjun; Zheng, Chunqiu; Zhou, Yuan; Zhu, Zhenkun; Hu, Zhao; Cao, Qiang; Wu, Sujuan; Zhang, Jing; et al.
Abstract : In this work, cesium salts with functional anions of acetate (Ac − ), fluoride (F − ) and trifluoroacetate (TFA − ) are explored to modulate the deposition of ZnO films in low-temperature carbon-based CsPbI2 Br perovskite solar cells. Abstract : Zinc oxide (ZnO) is an appealing electron transport layer for inorganic perovskite solar cells (IPSCs). However, attempts to achieve high device performance have been undermined by the imperfections at the ZnO/perovskite interface, including the intrinsic defects of ZnO and the nonideal contact between ZnO and perovskite films, which can cause severe interfacial recombination losses. With the purpose of resolving these problems, cesium salts with functional anions of acetate (Ac − ), fluoride (F − ) and trifluoroacetate (TFA − ) are explored to modulate the deposition of ZnO films. It is evidenced that these functional anions can coordinate with both Zn 2+ and Pb 2+ ions, causing defect passivation of the ZnO and the top perovskite films to different extents. Meanwhile, the Cs + ions can reduce the hydroxyl defects and form an interfacial dipole on the surface of ZnO via Zn–O–Cs bonds. Therefore, more stable and efficient interfacial electron transport can be established. Accordingly, we obtained a maximum power conversion efficiency (PCE) of 14.25% in low-temperature carbon-based IPSCs (C-IPSCs) using a CsPbI2 Br light absorber. This PCE is the highest value among all the ZnO-based C-IPSCs reported to date. Moreover, the corresponding devices without encapsulation demonstrate improved long-term stability in ambient air.